Responsible automedication in students of Health Sciences, Universidad Nacional Hermilio Valdizán - Morales-Ysuhuaylas, José L. (2019)
Objective: To determine the relationship between knowledge, attitudes and practice on responsible self-medication in the Health Sciences students of the Universidad Nacional Hermilio Valdizán de Huánuco in 2017. Methods: A transversal descriptive study was carried out in 214 students of the last academic year of the Professional Careers of Health Sciences (Human Medicine, Nursing, Psychology, Dentistry and Obstetrics). A questionnaire of 13 questions was used to assess knowledge, attitudes and practices regarding responsible self-medication, as well as important epidemiological data. The statistical analysis was performed using the chi-square test and the SPSS and Microsoft Excel programs for data processing. Results: Of the total of interviewees, 100% self-medicated, and of these 90.7% do so irresponsibly. A notable difference was found between the level of knowledge, with the little knowledge on the subject being the highest percentage, 71%. An association was found between attitude and responsible self-medication (p = 0.018). There was also an association between the type of university medical career and responsible self-medication (p = 0.014) and, finally, there was no association between responsible self-medication and level of knowledge, as well as the practices. Conclusions: A relationship was found between attitude and responsible self-medication in fifth-year students of health sciences.